Sensitivity Sector State-Owned Banking towards Signal Policy Fiscal: Event Study Change of Finance Minister on Himbara Banks Shares - Nidrah, Nidrah; Rika Kurniawati; Fitriani Rahim (Sean Institute, 2025)
The capital market serves as an important indicator for capturing informational changes, including political events related to fiscal policy. The announcement of a new Minister of Finance is considered an information event that may influence investor perceptions due to the strategic role of this position in determining national economic direction and fiscal stability. This study aims to examine the capital market reaction to the announcement, focusing on state-owned bank stocks (Himbara Banks) listed on the Indonesia Stock Exchange. An event study method was employed with an eleven-day event window (T–5 to T+5). The analysis utilized One Sample T-Test to detect significant abnormal returns on each observation day and Paired Sample T-Test to compare mean abnormal returns before and after the event. The findings reveal significant abnormal returns on T–3, T+3, and T+5, indicating that the market responded noticeably to the political event. The reaction on T–3 suggests possible information leakage, while the reactions on T+3 and T+5 reflect delayed market assessment of the new fiscal policy’s impact on state-owned banks. However, the Paired Sample T-Test indicates no significant difference between average abnormal returns before and after the announcement. These results suggest that the Indonesian capital market has not yet achieved semi-strong form efficiency.